Understanding Thai Teachers’ Perception of Self-Regulation From an Attachment Perspective - Likhitsuwan, Pichaya (2024)
Self-regulation is defined as the process that incorporates emotion, attention, behavior, and cognition altogether with the aim of bringing the body from a dysregulated state and return to the regulated state. Secure attachment experiences shape formation of healthy internal working models that leads to development of adaptive self-regulation skills. In the classroom context, teachers are important to further development of children’s self-regulation. However, teachers’ understanding of self-regulation is rarely examined through the lens of attachment. Through an ethnographic study from working as a classroom kindergarten teacher for five months, data in this research is derived from semi-structured interviews of three Thai kindergarten classroom teachers. Thematic analysis is selected as the method of analysis. The findings revealed that Thai kindergarten teachers generally under-stand the effects of past experiences on the developmental process of children’ self-regulation. They also have appropriate level of emotional support and classroom management that promote self-regulation in children. The aim of this research is to explore how self-regulation is understood and aiding educators in expanding their capacity to support their students in developing independent self-regulation skills, while maintaining cultural sensitivity to how such skills are developed among children from diverse backgrounds.